2007
DOI: 10.1089/ten.2006.0329
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Epidermal Constructs on a Collagen Layer Alone

Abstract: Because engineered tissues are designed for clinical applications in humans, a major problem is the contamination of cocultures and tissues by allogenic molecules used to grow stem cells in vitro. The protocols that are commonly applied to generate epidermal equivalents in vitro require the use of irradiated murine fibroblasts as a feeder layer for keratinocytes. In this study, we report a simple procedure for growing human keratinocytes, isolated from adult skin, to generate an epidermal construct on a collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
(76 reference statements)
2
8
0
Order By: Relevance
“…It is known that fibroblasts play key roles promoting keratinocyte growth and differentiation . Additionally, the presence of calcium, serum, or both, can induce keratinocyte proliferation and differentiation . These observations are in agreement with the obtained results that clearly showed the rearrangement and phenotypic variations of hKC to be dependent on the presence of hDFb and serum in the heterotypic culture established in KSFM/MEM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is known that fibroblasts play key roles promoting keratinocyte growth and differentiation . Additionally, the presence of calcium, serum, or both, can induce keratinocyte proliferation and differentiation . These observations are in agreement with the obtained results that clearly showed the rearrangement and phenotypic variations of hKC to be dependent on the presence of hDFb and serum in the heterotypic culture established in KSFM/MEM.…”
Section: Discussionsupporting
confidence: 92%
“…[15,58] Additionally, the presence of calcium, serum, or both, can induce keratinocyte proliferation and differentiation. [59,60] These observations are in agreement with the obtained results that clearly showed the rearrangement and phenotypic variations of hKC to be dependent on the presence of hDFb and serum in the heterotypic culture established in KSFM/MEM. In fact when culturing with KSFM/MEM, proliferative Ki-67 positive hKC were detected in the basal layer.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the total duration of culture, the passage number of cells and the assumptive total cell output, all suggested that the induced cells had longterm growth potential. Intriguingly, the most significant characteristic of the induced cells was their ability to regenerate a stratified skin equivalent [Riva et al, 2007]. These results demonstrated that the morphologic, phenotypic, growth and functional characteristics of the activator-induced cells were very similar to those of epidermal stem cells, i.e.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, the total days of culture, the passage number of cells, and assumptive total cell output all suggested that dedifferentiation‐derived cells, as well as epidermal stem cells, had long‐term growth potential. Intriguingly, the most significant characteristic of dedifferentiation‐derived cells was their ability to regenerate a highly stratified skin equivalents [38]. These results demonstrated that the phenotypic and functional characteristics of dedifferentiation‐derived cells cultured in vitro were similar to epidermal stem cells.…”
Section: Discussionmentioning
confidence: 93%